Female Labor Force Participation in Latin America: Patterns and Explanations - Matias Busso; Dario Romero Fonseca (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
Female labor force participation has increased 10 percentage points between 1990 and 2010. This paper analyzes the possible determinants of this increase. Among those determinants are changes in education, family structure, fertility, as well as changes in socioeconomic environment including wages, returns to working at home, preferences, and technology, among others. We discuss the mechanisms behind those determinants by organizing the very large theoretical and empirical literature on the subject. We then assess the relative importance of the determinants in two ways. We compute treatment effects estimated in the literature and combine them with information about the changes in the causing variables. We also use data from household surveys and combine them with a dataset of determinants to find correlations in the data that reinforce or reject the analysis of the literature review.
Keywords: J22; J16; N3; 330; Female labor supply; Latin America; Determinants; Literature Review